ANTI-BACTERIAL AND ANTI Β-LACTAMASE ACTIVITIES OF EUPHORBIA HIRTA AND TRIDAX PROCUMBENS AGAINST CLINICAL ISOLATES OF Β-LACTAMASE PRODUCING SALMONELLA ENTERICA AND STAPHYLOCOCCUS AUREUS - Haroun, Ahmed A.; Vantsawa, Philip Anthony; Awujoola, Abidemi Elizabeth (FUDMA Journal of Sciences, 2026)
This study investigated the antibacterial and anti-β-lactamase activities of Euphorbia hirta and Tridax procumbens against clinical isolates of β-lactamase-producing Salmonella enterica and Staphylococcus aureus, addressing the growing challenge of antibiotic resistance to β-lactam antibiotics. A total of 200 clinical specimens, comprising 100 nasal swabs and 100 stool samples, were collected. From these, 24 isolates of S. enterica and 20 isolates of S. aureus were recovered and microbiologically characterized using standard biochemical tests. S. aureus was confirmed by positive catalase and coagulase reactions, while S. enterica showed motility, citrate utilization, and hydrogen sulfide production. Antibiotic susceptibility testing revealed high resistance levels to commonly used β-lactam antibiotics, with S. enterica exhibiting up to 100% resistance to cefuroxime and S. aureus showing up to 95% resistance. β-lactamase screening indicated high pre-exposure enzyme production in both organisms (83.3% and 85%, respectively). Phytochemical screening showed that E. hirta contained glycosides, tannins, saponins, and phenols, whereas T. procumbens contained mainly glycosides. Antibacterial assessment demonstrated that both plant extracts produced mild to moderate inhibitory effects at 600 mg/dL. Ethanolic extracts showed slightly higher activity (8–9 mm inhibition zones) than aqueous extracts (6–8 mm). However, post-exposure evaluation revealed limited anti-β-lactamase activity, with most isolates remaining β-lactamase-positive. In conclusion, although the extracts exhibited moderate antibacterial activity, their minimal anti-β-lactamase effect suggests that they may function better as supportive or complementary agents rather than standalone treatments. Further studies are recommended to isolate active compounds and assess synergistic interactions with existing antibiotics.
Keywords: Phytochemical analysis; Staphylococcus aureus; Salmonella enterica; Antimicrobial resistance; Tridax procumbens; β-lactamase-producing bacteria